Knowledge, attitude, and practice regarding different domains of pediatric obstructive sleep apnea among pediatric dentists from Kerala: A cross-sectional study - Lekshmy S R. Nair; Sageena George; S Anandaraj; Joby Peter; R A Soorya; Shiad Salim (Wolters Kluwer Medknow Publications, 2023)
Background: Pediatric dentists should play an essential role in obstructive sleep apnea (OSA) screening, referral, and management of their child patients. However, few studies have investigated pediatric dentists' knowledge, attitude, and practice aspects regarding different domains of pediatric OSA. Aim of the Study: This cross-sectional survey aimed to assess the knowledge, attitude, and practice aspects of different domains of pediatric OSA among pediatric dentists from Kerala. Methods: This cross-sectional study was conducted in Kerala. The sample frame consisted of 163 dentists, and the minimum required was 115. Ethical approval was obtained before starting the study. Settings and Design: An invitation E-mail explaining the purpose of the study with a survey link was sent to the pediatric dentists from Kerala (n = 163). Nonrespondents were contacted at timely intervals. Statistical Analysis: Categorical and quantitative variables were expressed as frequency (percentage) and mean ± standard deviation, respectively. Chi-square test was used to find an association between categorical variables. Statistical analysis was performed using a statistical software package, SPSS, version 20.0. Results and Conclusion: This cross-sectional study showed that pediatric dentists in Kerala have a moderate-to-good level of knowledge, along with a positive attitude toward different domains of pediatric OSA, but lag behind in the practice aspects. Hence, they are required to direct themselves toward continuing dental education programs in order to boost their routine practice. For this, steps must be taken to ensure proper networking of the practitioners and amendments in the dental billing system similar to the medical counterpart.